Impact of forest fires generated black carbon deposition fluxes in Great Hinggan Mountains (China). (29th November 2017) - Gao, Chuanyu; He, Jiabao; Cong, Jinxin; Zhang, Shaoqing; Wang, Guoping
Abstract: Black carbon is produced by incomplete combustion of fossil fuels and biomass. The production of black carbon over the last several centuries has been primarily influenced by human activities. Human exploitation of forest resources, together with increases in regional fire frequency and intensity, can increase regional black carbon emissions and can led more black carbon deposited into natural ecosystem. Here, based on 210 Pb age‐depth model, we investigated black carbon deposition over several key periods in the last 150 years in 5 peatlands of the Great Hinggan Mountains (Northeast China), an area that has been exploited by humans without forest protection policies. The results showed that average black carbon deposition fluxes from different peatlands in the Great Hinggan Mountains were 1.1 to 4.8 mg·year −1 ·cm −2, which were similar to other peatland distribution regions and higher than other ecosystems. Frequent and intense fire events during the exploitation period led to regional peak black carbon deposition before the 1980s. After the 1980s, fire events were controlled, and the government implemented forest protection policies that decreased the trend in regional fire frequency in the Great Hinggan Mountains and markedly decreased black carbon deposition. Fire events controlled by regional human activities are therefore the major factor that influence regional black carbon deposition fluxes, and frequent forest fires could increase black carbon deposition fluxes in surrounding ecosystem.